STATE OF THE ART REVIEW: PJBL, DEEP LEARNING, AND CRITICAL THINKING: A CAUSALITY MODEL FOR 21ST CENTURY COMPETENCIES - Marwiyah Nst, Masringgit; Festiyed, Festiyed; Yerimadesi, Yerimadesi (JURNAL TARBIYAH, 2025)
This research focuses on the urgency of improving students' critical thinking skills, recognized as a crucial competency for facing 21st-century challenges. To address this challenge, the Project-Based Learning (PjBL) model has been identified as a strategic and effective pedagogical approach for fostering higher-order cognitive abilities. Previous literature has confirmed the positive contribution of PjBL to learning outcomes, but there is a significant research gap regarding the exploration of the internal mechanisms underlying this success, namely Deep Learning. Deep Learning, which involves comprehensive understanding of meaning rather than mere memorization, is a crucial prerequisite for the authentic and transferable development of students' critical thinking skills. Therefore, the primary objective of this research is to empirically test and analyze the effect of the PjBL model on improving students' critical thinking skills in relation to the quality of the Deep Learning it facilitates. Using a quasi-experimental method, the results of this study are expected to provide clear theoretical and practical contributions, demonstrating that the effectiveness of PjBL in improving critical thinking skills stems from its ability to encourage students to engage in deeper knowledge processing.